2011
DOI: 10.1186/1472-6963-11-4
|View full text |Cite
|
Sign up to set email alerts
|

Preventing hospital admissions by reviewing medication (PHARM) in primary care: design of the cluster randomised, controlled, multi-centre PHARM-study

Abstract: BackgroundMedication can be effective but can also be harmful and even cause hospital admissions. Medication review or pharmacotherapy review has often been proposed as a solution to prevent these admissions and to improve the effectiveness and safety of pharmacotherapy. However, most published randomised controlled trials on pharmacotherapy reviews showed no or little effect on morbidity and mortality. Therefore we designed the PHARM (Preventing Hospital Admissions by Reviewing Medication)-study with the obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 23 publications
0
28
0
3
Order By: Relevance
“…The effect of a multicomponent pharmaceutical care intervention on medication‐related hospital admissions was studied in an open controlled design. The study protocol is described in detail elsewhere . The study protocol was approved by the medical ethical review board METOPP [‘Medisch Ethische Toetsing Onderzoek Patiënten en Proefpersonen' (medical–ethical assessment of studies involving patients or healthy volunteers)].…”
Section: Methodsmentioning
confidence: 99%
“…The effect of a multicomponent pharmaceutical care intervention on medication‐related hospital admissions was studied in an open controlled design. The study protocol is described in detail elsewhere . The study protocol was approved by the medical ethical review board METOPP [‘Medisch Ethische Toetsing Onderzoek Patiënten en Proefpersonen' (medical–ethical assessment of studies involving patients or healthy volunteers)].…”
Section: Methodsmentioning
confidence: 99%
“…Several broad recommendations for the reduction of preventable DRVs have been proposed such as improving communication between acute and ambulatory health care providers when patients transition between care settings; conducting regular review of prescription medications to avoid therapeutic duplication and to discontinue unnecessary drugs; advising patients to frequent one community pharmacy and to discuss self-selection of over-the-counter (OTC) and herbal therapy with a pharmacist or physician [9]–[11]. Enhanced patient monitoring is also frequently suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that adverse drug events are a common cause for hospitalisations and how medication reviews might have an impact on such hospitalisations 1 8 9 24 25. In the HARM (Hospital Admissions Related to Medication) study, Leendertse et al 8 found that up to 46% of the drug-related hospital admissions were preventable; based on their findings, they recommended the performance of regular medication reviews to improve that outcome.…”
Section: Discussionmentioning
confidence: 99%